Numerical analysis of optical bistability based on Fiber Bragg Grating cavity containing a high nonlinearity doped-fiber - Zang, Zhigang (Optics communications, 2012)
We demonstrate a new optical bistability devise by using two Fiber Bragg Gratings (FBG), in which an erbium-doped fiber (EDF) is inserted to form a nonlinear Fabry–Perot cavity (EDF FBG/F–P). The operation principle of this device is described by the resonant nonlinearity theory combining with the transfer matrix method. The optical bistability behaviors under different parameters are investigated. It shows that EDF FBG/F–P device has an evident merit in reducing the threshold switching power to 7 mW, resulting in a reduction about 6 orders, compared with that of single FBG device. Moreover, the ultra-fast response time about 35 ps is also confirmed.